“In-situ” x-ray imaging technology for material and manufacturing science: a review - Nguyen, Van Anh; Le, Duy Han; Damian, Dilen; Tran, The Bach; Le, Quang Hung; Nguyen, Nhu Tung (Elsevier, 2025)
“In-situ” X-ray imaging has become a powerful tool in materials and manufacturing science, enabling real-time observation of critical processes. However, access to X-ray facilities remains highly competitive due to limited availability, high operational costs, and technical complexity, restricting its use to a few research groups worldwide. This review addresses this challenge by providing a comprehensive analysis of X-ray imaging technologies, their historical development, and recent advancements in “in-situ” X-ray imaging. It explores applications across various materials and manufacturing processes, including welding, additive manufacturing (AM), casting, high-temperature furnaces, and novel materials. Key topics such as heat transfer, melt pool dynamics, solidification, microstructure evolution, and defect formation in manufacturing processes are systematically examined. Additionally, the review highlights the potential of “in-situ” X-ray imaging for discovering novel materials and advancing manufacturing technologies. It discusses current limitations, particularly the constraints of existing X-ray facilities, and outlines future directions for enhancing this technology. Expanding access to high-resolution X-ray imaging is crucial for accelerating advancements in materials and manufacturing. Integrating artificial intelligence and simulation models will further enhance its capabilities. Achieving these improvements requires upgrading existing X-ray facilities and developing new systems capable of capturing high-resolution, real-time imaging of complex material processes.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; Industrial Engineering & Automation; 4014 Manufacturing engineering; 4017 Mechanical engineering